The Role of Culinary Tourism towards the Preservation of Traditional Food: A Study of the Local Restaurant Kantin Palmes - Asep Parantika; Muhammad Firdaus Raflikeza; Achmad Iqbal Rivai (Bogor Hospitality Journal, 2025)
Culinary tourism is an effective means of preserving traditional food in the midst of modernization and globalization. This research examines the role of local restaurant Kantin Palmes in Pekalongan in preserving traditional foods such as Soto Pekalongan, Pindang Tetel, and Nasi Megono. The research objective is to analyze the contribution of Kantin Palmes' culinary tourism to the preservation of traditional food and identify the challenges faced. Using a qualitative approach, data was obtained through direct observation and visitor reviews on online platforms. The results showed that Kantin Palmes supports traditional culinary preservation through serving specialties with cultural and historical value. However, challenges such as the unavailability of a consistent menu, the lack of cultural elements in the decor, and competition with modern food are the main obstacles. Culture-based strategies, such as local elements in restaurant design, improved menu consistency, and product diversification that maintains traditional identity, are proposed as solutions. In addition, collaboration with local MSMEs can strengthen the local economy and preserve culture. This research provides insights for local restaurant managers and local governments in developing sustainable culinary tourism. Further research is recommended to explore various culinary destinations in Indonesia to understand the pattern of traditional food preservation more broadly.